Le Québec élève-modèle du Canada dans le dossier des émissions de gaz à effet de serre : concours de circonstances ou l’exemple à suivre? - Sebastian Weissenberger (VertigO)
Quebec’s greenhouse gas (GHG) emissions are, on a per capita basis well below the Canadian average and close to those of developed European countries. The availability of zero-emission hydroelectric energy enables Quebec to keep its emissions at the level of those European countries, although its per capita energy consumption is twice as high as theirs and similar to that of Canada or the United States. However, hydroelectricity only partly explains the lower emissions of Quebec with respect to the Canadian average. The absence of a fossil fuel extraction sector and lower emissions in other sectors such as transport, agriculture and industry also contribute to this trend. An analysis of energy sector indicators over the past two decades suggests that advances in industrial technology, as in the case of the aluminum and magnesium industry and oil prices are far better regulators of greenhouse gas emissions than government policies designed to incite emission reductions. The low energy efficiency and experiences of other countries lead to believe that economic incentives would uncover a significant potential of greenhouse gas emissions through the reduction of energy consumption. In the forthcoming Canadian plan for the implementation of the Kyoto objectives, Quebec should be credited for its lesser emissions and their increase rate and be compelled to follow a less steep emission reduction curve than other provinces with less advantageous GHG budgets.